USE CASE - METHOD PROFESSIONAL DISCIPLINES FUTURE ECONOMISTS. - O. N. Goncharova; G. E. Cheporova (Kherson State University, 2010)
The article is considered the features analysis of Case Study method of students teaching applicating information-communications technologies. Author's experience of Case Study method application in the educational process is considered on economic specialities.